2001
DOI: 10.1046/j.1365-2214.2001.00194.x
|View full text |Cite
|
Sign up to set email alerts
|

School peer relationships of ‘minority’ children in Scotland

Abstract: This paper examines selected issues arising from two studies in mainstream education of two minority groupings of children in Scotland-those with serious medical conditions and refugee children-completed in 1997 and 1999, respectively. It draws on first-person accounts of children, parents and teachers and focuses on school-based peer relationships, including friendships. Many of the described peer experiences were unhappy or mixed, only a minority were positive. The paper relates the research and its findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 2 publications
0
21
0
Order By: Relevance
“…According to French and Swain (2004), the voices of disabled people in these accounts of inclusion and special education are slowly becoming more prominent. When children's voices are heard, they frequently tell a story of marginalisation, being left out or denied 'ordinary' educational experiences (for example, Closs et al 2001;French and Swain 2004;Lightfoot, Wright, and Sloper 1999;Shakespeare, Priestley, and Barnes, n.d.).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…According to French and Swain (2004), the voices of disabled people in these accounts of inclusion and special education are slowly becoming more prominent. When children's voices are heard, they frequently tell a story of marginalisation, being left out or denied 'ordinary' educational experiences (for example, Closs et al 2001;French and Swain 2004;Lightfoot, Wright, and Sloper 1999;Shakespeare, Priestley, and Barnes, n.d.).…”
Section: Introductionmentioning
confidence: 97%
“…Lightfoot, Wright, and Sloper (1999) reported that adolescents with chronic health conditions also experienced social isolation, exclusion from peer activities, and felt 'different' in classroom activities. Closs et al (2001) suggested that the discriminatory attitudes and expectancies of other children in schools lead to stigmatisation and marginalisation in the school social context. Yet this research also highlights variation in individual experiences of inclusion and exclusion.…”
Section: Introductionmentioning
confidence: 98%
“…In an Icelandic study on children's friendship(s), most children in fifth through seventh grade (67%) found themselves to have many friends at school (14). Children with a chronic health condition, like medical conditions (15) and autism (16) have been found to have poorer quality of friendship(s) than children without chronic health conditions. No study was found that evaluated the relationship between friendships and QOL among school‐age children.…”
Section: Introductionmentioning
confidence: 99%
“…2003). Furthermore, experiences of violence and persecution may lead to difficulties with identity and integration in the new country (Closs et al . 2001; Fantino & Colak 2001).…”
Section: Introductionmentioning
confidence: 99%